MENGGAGAS KONSEP TEOLOGI KEKINIAN DI ERA INDUSTRI 4.0 - Kholidah Nur (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2019)
At present it is often referred to as the era of the Industrial Revolution 4.0. This era was marked by the widespread process of digitalization of all dimensions of human life. None of the traces of humans today are separated from digital recordings, including the field of theology. Mankind has shifted to the digital field to understand the theological aspects and more or less has an effect on human belief in theological values. Therefore, new ideas are needed to answer the issue of parish theology in this era of Industrial Revolution 4.0. The theology of the present, say so, must be able to provide enlightenment and understanding that does not come out of the core of Islamic theology, namely monotheism.